Effectiveness of probiotic feed ingredient on the growth performance of broiler - GNIKPO, Aristide; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; HOUNDONOUGBO, PASCAL VENANT; ADENILE, D. A.; DOUGNON, T. Jacques; CODJIA, JEAN TIMOTHE CLAUDE (My University, 2016)
The use of antibiotics in human or veterinary therapy is followed by the appearance of bacteria resistance to these antibiotics. This is a serious problem because of the direct impact on therapeutic possibilities. This study aimed at evaluating the efficiency of a probiotic feed ingredient (Starter) on the growth performance of broiler (Hubbard) to allow a reduction of the use of antibiotics. The experimental design consists of four treatments with three replications: diets with 0%, 1.5%, 3% and 4.5% of the probiotic feed ingredient. Each replication consists of 18 broilers with an average live body weight of 43.04 ± 6.38 g. After seven (7) weeks of trial, chickens receiving the treatment .T1.5 had the best growth with an average weight of 984.22 ± 249.2 g, but with no significant difference (P> 0.05). In this treatment, their feed intake was the highest (51.38 g/bird/day) while the feed conversion rate turned out to be the lowest (6.67 g feed/g Live body weight). The highest value of carcass yield (76.1%) and sternum proportion (5.54%) were obtained in treatment T3. From the above results, we can state that the probiotic feed ingredient included at 1.5% and 3% improved growth performance of broilers. It could help to significantly improve the production performance of broilers if its probiotics properties are enhanced.
Keywords: Broiler; feeding; tchoukoutou; kpètè-kpètè; carcass yield